The usage of system dynamics in regional sciences - Sobotková, Lucie (Univerzita Pardubice, 2011)
The paper deals with presentation of system dynamics as the tool for modeling of economic processes. The model of regional competitiveness is used for closer characteristics of this discipline. The system dynamics enables to search and mutually to combine “hard” and “soft” processes in regional economy. The searching retroactive reactions of elements of system to interference with regional economy is the next important character.
Keywords: regions; competitiveness of regions; system dynamics; model of competitiveness; simulation of model